Assistance for Oyster Mushroom Entrepreneurs in Making Fish Feed Formulations for African Night Crawler Worm (ANC) and Trichoderma sp. Fermented Bran - Dini, Isna Rahma; Saputra, Rachmad; Hapsoh, Hapsoh; Salbiah, Desita; Yoseva, Sri; Masjudi, Heri (Talenta Publisher Universitas Sumatera Utara, 2023)
Utilization of baglog waste as a growth medium for ANC worms as a raw material for making formulated fish feed provides opportunities as a side business for oyster mushroom entrepreneurs to increase income. The purpose of this service is to provide assistance to target partners, in this case oyster mushroom entrepreneurs, in utilizing ANC worm flour as a substitute for fish meal and then formulated with Trichoderma sp. fermented bran. The results of the dedication that has been carried out show that there has been an increase in partners' skills in making formulated fish fefazidah@usu.ac.ided and developing the potential of science and technology-based independent entrepreneurs who develop from mushroom businesses. After this dedication, it is hoped that the partners can continue to develop this worm farming business and the application of worm-formulated feed for fish farming which has also been developed by partners so as to create an integrated oyster mushroom-based farming center.